Nineteenth Meeting of the National Development Council Summary Record New Delhi November 4 and 5 1962 - Planning Commission (Planning Commission, 1962)
The Plan has been the major instrument in the economic and social reconstruction of the country. In the new situation, the Plan must fulfil this purpose even more directly and in terms of action and results in the short period. Certain priorities in the Plan have necessarily to be rearranged and adapted to meet the present requirements. In several directions the effort under the Plan will need to be strengthened. In all fields implementation must become much more efficient. For a period, a number of activities, important in themselves and for long term development, will have to be deferred or scaled down. The various adjustments which are called for should be made without delay as speedily as possible, but always in a planned and well-considered manner and keeping in view the overall national interest.
National Development Council
Government of India Planning Commission
Keywords: Strengthening of Planning Machinery in the States; Organization for prices and civil supplies; Mobilization of resources and saving; Review and rephrasing of projects; Trained manpower; Economies in construction; Intensification of agricultural production; Organization of production through small industries; Selective approach in social services; Efficiency in administration and implementation.